2020
DOI: 10.1103/physreve.102.053101
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory rivers adjust their shape to sediment transport

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 31 publications
5
42
0
Order By: Relevance
“…In the laminar regime, a wide range of slope values are possible. For example, laminar river analogs have been observed to have 1.5-2.5 times higher slopes than their natural counterparts (Malverti et al, 2008) and others have also reported values such as 0.1 (Delorme et al, 2018) and 5 × 10 −3 (Abramian et al, 2020). In the context of our experiments, such analyses suggest that temperature gradients in laminar flows can have values that differ from the fully turbulent analogs but nevertheless still recreate specific morphologies.…”
Section: Surface Tensionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the laminar regime, a wide range of slope values are possible. For example, laminar river analogs have been observed to have 1.5-2.5 times higher slopes than their natural counterparts (Malverti et al, 2008) and others have also reported values such as 0.1 (Delorme et al, 2018) and 5 × 10 −3 (Abramian et al, 2020). In the context of our experiments, such analyses suggest that temperature gradients in laminar flows can have values that differ from the fully turbulent analogs but nevertheless still recreate specific morphologies.…”
Section: Surface Tensionsupporting
confidence: 57%
“…The quintessential example of a meandering channel is the alluvial river, which forms and evolves by erosion and deposition of sediment (e.g., Fisk, 1944;Seminara, 2006) and interaction with riparian vegetation (e.g., Braudrick et al, 2009). Meandering channels also form in bedrock where the driving processes include dissolution (e.g., Veress and Tóth, 2004;Allen, 1971;Zeller, 1967), abrasion by sediment particles (Sklar and Dietrich, 2004), plucking of bedrock (Chatanantavet and Parker, 2009;Whipple et al, 2000), slaking (Johnson and Finnegan, 2015), and weathering (Pelletier and Baker, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Parker's formulation, channel geometry is fundamentally determined by hydraulics. An alternative model was recently proposed by researchers from the Institut de Physique du Globe de Paris (IPGP), in which channel shape, under laminar flow conditions, is adjusted to achieve a balance between lateral diffusion of bed-load flux toward the channel margins, and inward sediment motion due to gravity 51 . In this formulation, raising the imposed sediment discharge drives increases in channel aspect ratio (W /H) and slope, away from the threshold state associated with no sediment flux (Fig.…”
Section: /36mentioning
confidence: 99%
“…Early research linked fluid mechanics with alluvial channel geometry [45][46][47] through the development of flow resistance relations in threshold canals, designed to convey water while never exceeding the entrainment threshold. Building on canal theory 46,48,49 , a family of models has been advanced in which sediment transport is formally treated as a mathematical perturbation to the threshold state [50][51][52] . Though different in detail, these models indicate that alluvial rivers at bankfull organize their geometry such that fluid shear stresses at the channel center only slightly exceed the entrainment threshold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation